Peningkatan Minat Guru Pada Perencanaan Penelitian Tindakan Kelas Berkarakter Pembelajaran Abad-21 - Waluyo, Waluyo; Sukatiman, Sukatiman (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
There are approximately 20% of the teachers of SMKN I Jenar who have non-educational backgrounds (Pure Science), and more than 30% of young teachers have not received PPG training. One of the impacts of weak basic pedagogic competencies will affect the success of education so that it is necessary to deepen Classroom Action Research (CAR). This service aims to provide a deepening of teacher knowledge about Classroom Action Research (CAR) to improve their learning. The implementation method is carried out by deepening the Classroom Action Research (CAR), and guiding the making of Classroom Action Research (CAR) proposals. The implementation of the service is carried out by several PTB study lecturers, in the context of UNS Anniversary with the UNS Teaching program Indonesia. Expected targets: The Teachers can design 70% CAR in the material they teach.